Soya oil as alternative fuel for diesel engine. - Manegdeg, Ferdinand G.
The increasing concern on energy resources and the environment leads to a detailed analysis on the performance, emission and economy of compression ignition engine using alternative fuels. The objective of this paper is to present and compare the performance and emission characteristics of diesel oil and soya oil as an alternative fuel over a range of compression ratio at constant speed and injection rate and at the experimented optimum injection advance for maximum power in a compression ignition engine. Results of the fuel property measurements indicate that the empirical chemical symbol of soya oil is C13H22.6O12 while diesel oil is C14.4H26.l. Soya oil can release 87 percent of the energy released by diesel oil. Soya oil has higher optimum injection advance for each compression ratio. Operating at optimum injection advance for maximum power and at higher compression ratios (r=19:1, 20:1), the brake mean effective pressure of soya oil is 95 percent of the brake mean effective pressure produced by diesel oil, and soya oil is 10 percent less thermally efficient than diesel oil.